The heist : a novel - Evanovich, Janet; Goldberg, Lee, 1962- (2013)
Just when it seems that international crook Nicolas Fox has been captured for good, he pulls off his greatest con of all: he convinces the FBI to offer him a job, working side by side with Special Agent Kate O'Hare. Problem is, teaming up to stop a corrupt investment banker who's hiding on a private island in Indonesia is going to test O'Hare's patience and Fox's skill -- if the two don't kill each other first.
Keywords: Islands -- Indonesia -- Fiction; Investment banking -- Corrupt practices -- Fiction; Swindlers and swindling -- Fiction